2020
DOI: 10.1111/ner.13109
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Directional Deep Brain Stimulation in Essential and Parkinsonian Tremor

Abstract: Objective To compare directional monopolar, bipolar, and directional bipolar thalamic deep brain stimulation (DBS) in tremor patients. Methods Fourteen tremor patients (7 Essential Tremor and 7 Parkinson's Disease) implanted with directional DBS electrodes in the ventral intermediate nucleus (VIM) were enrolled. Side‐effect thresholds of monopolar directional stimulation (DIRECT) were compared to circular DBS as well as, in a randomized design, to those of two different bipolar stimulation settings (BIPOLAR = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…A number of studies using directional DBS leads (d-leads) in the Vim for tremor (15)(16)(17)22) and the STN for Parkinson's disease have been published (16,(23)(24)(25)(26). Most demonstrated a theoretical superiority of d-leads over standard leads with a wider therapeutic window and lower therapeutic current strength or lower total electric energy delivered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies using directional DBS leads (d-leads) in the Vim for tremor (15)(16)(17)22) and the STN for Parkinson's disease have been published (16,(23)(24)(25)(26). Most demonstrated a theoretical superiority of d-leads over standard leads with a wider therapeutic window and lower therapeutic current strength or lower total electric energy delivered.…”
Section: Discussionmentioning
confidence: 99%
“…All leads ( n = 12) were replaced within 2 mm of the original lead and none were excluded from the study. Patients received a rotational fluoroscopy using a flat panel detector C‐arm system (Allura Xper FD20; Phillips Healthcare) three days to three weeks after surgery to determine the rotational orientation of the directional leads (21).…”
Section: Methodsmentioning
confidence: 99%
“…Directional deep brain stimulation (DBS) with radially segmented leads is a novel technique that facilitates steering the electric field in the axial plane; the stimulation thus conforms better to the target volume and avoids current spread to non-target tissue [1][2][3]. Although several studies have confirmed that directional DBS can help reduce side effects and widen the therapeutic window [4][5][6][7][8], programming directional DBS remains complex due to the number of possible stimulation settings. It has been pointed out that precise knowledge of the orientation of the segmented electrode can help to find the optimal stimulation parameters and understand the observed DOI: 10.1159/000510883 stimulation effects [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Subthalamic nucleus (STN) deep brain stimulation (DBS) is a safe and effective treatment option improving quality of life (QoL) [18], motor [28], and non-motor symptoms (NMS) [14] in patients with advanced Parkinson's disease (PD) who suffer from motor complications or pharmacotherapy-refractory tremor [46].…”
Section: Introductionmentioning
confidence: 99%